2020
DOI: 10.1177/2325967120942133
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Failure Mode Between Simple and Mattress Suture Configuration in Arthroscopic Bankart Repairs: A Cadaveric Study

Abstract: Background: Traumatic anterior shoulder dislocations disrupt the anteroinferior labrum (Bankart lesion), leading to high rates of instability and functional disability, necessitating stabilization. Purpose: To investigate modes and locations of repair failure between simple and horizontal mattress suture configurations after arthroscopic Bankart repair using suture anchors in a cadaveric model. Study Design: Controlled laboratory study. Methods: A total of 48 fresh-frozen human cadaveric shoulders from 48 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Of these, 1255 were excluded after reading the title or abstract and 31 were excluded after a full-text review. Ultimately, six biomechanical studies [ 5 , 7 , 14 , 15 , 21 , 22 ] were included in this systematic review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 1255 were excluded after reading the title or abstract and 31 were excluded after a full-text review. Ultimately, six biomechanical studies [ 5 , 7 , 14 , 15 , 21 , 22 ] were included in this systematic review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All six biomechanical studies were controlled laboratory studies. Of these six studies, three [ 14 , 15 , 21 ] compared horizontal mattress repair with simple repair, two [ 5 , 22 ] compared double-row repair with simple single-row repair, and one [ 7 ] compared horizontal mattress repair, simple single-row repair, and double-row repair. The median QUACS scale for assessment of methodological quality was 11.5 with a range from 10 to 12, indicating a low risk of bias (Table 2 and Supplementary table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only may the type of anchor used for shoulder stabilization have an influence, but the suture configuration also has an influence on the resulting stability. In a cadaveric and biomechanical study, Miskovsky et al found that horizontal mattress suture configurations create a larger area of repair, decreasing the risk of repair failure at the labrum compared to simple suture configuration [ 20 ]. Similar findings were made by Hagstrom et al [ 21 ].…”
Section: Discussionmentioning
confidence: 99%